(untitled) (Revista de Medicina Clinica, 2022)
Subacute combined degeneration is a complication associated with vitamin B12 deficiency that mainly affects the posterior and lateral cords of the spinal cord at the cervicodorsal level. Subacute combined degeneration is associated with pernicious anemia and commonly with anti-intrinsic factor antibody disease, where prompt initiation of treatment is vital to achieve the reversal of present hematological alterations and neurological symptoms, but above all, to stop the progression of axonal damage. We present the case of a 68-year-old woman with a history of customary alcoholism, reporting progressive pain and weakness of the lower extremities, paresthesia, ataxia, and cognitive-behavioral disturbances. The diagnosis was suspected by the clinical data, the performance of neurophysiology studies that reported demyelinating peripheral neuropathy and was confirmed with positive serum levels of vitamin B12 and anti-intrinsic factor antibodies; the patient had an adequate evolution with the implementation of high-dose vitamin B12 replacement therapy as well as a diagnostic-therapeutic response to it.